Analysis of genetic diversity in pigeon pea (Cajanus cajan ) by using PCR based molecular marker - Shende, Sarika; Raut, Anand (Recent Research in Science and Technology, 2013)
Assessment of genetic diversity and identification of crop genotypes are essential for efficient conservation and utilization of germplasm resources. Random amplified polymorphic DNA (RAPD) was used to determine the genetic relationship among 15 pigeon pea genotypes. A total of 23 amplicons were detected with 5 primers of which 13 were polymorphic. The polymorphism shown by RAPD markers was 56.52%. The average polymorphic information content (PIC) value exhibited by RAPD was found to be 0.127. Genetic similarity values ranged from 22-98% with an average of 67%. A dendrogram based on the Jaccard’s similarity values showed distribution pattern of variability between genotypes with different morphological and agronomic traits.